Tingkat Kecemasan Mahasiswa Keperawatan Menjelang Pembelajaran Praktik Klinik - Elda Tania; Rimarsya Meyland Putri; Siti Nurazizah; Fitri Nurazizah; Satriya Pranata; Haifa Nahda Rizqi (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Clinical practice is a crucial stage in nursing education that requires students to apply theoretical knowledge in real healthcare settings. The transition to a clinical environment often triggers anxiety, as students face competency demands, professional responsibilities, and direct interactions with patients. This study aims to determine the anxiety levels of fifth-semester nursing students prior to clinical practice at Universitas Muhammadiyah Semarang. A descriptive quantitative design was employed with a sample of 35 students selected using a simple random sampling technique. Data were collected using the Hamilton Anxiety Rating Scale (HARS) and analyzed descriptively with Microsoft Excel to obtain frequency and percentage distributions. The results showed that most students experienced severe anxiety (31%), followed by moderate (29%), mild (23%), no anxiety (14%), and panic-level anxiety (3%). These findings indicate that the majority of nursing students experience anxiety before clinical practice, predominantly at severe and moderate levels. Therefore, psychological support and mental preparation programs are essential to help students transition optimally into the clinical environment.